PENDEKATAN SCAFFOLDING SEBAGAI UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA - Dwi Hasmidyani; Firmansyah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
This research aims to improve the activity and students learning outcomes in the learning of microeconomics with the material demand and supply through the scaffolding approach oriented problem solving (problem solving). The subjects of this study were 36 students of Economics Education FKIP Sriwijaya University second semester of academic year 2014/2015. The method used in this research is a classroom action research method that consists of four activities, planning, action, observation, and evaluation-reflection using scaffolding learning methods implemented in the third cycle. Data were collected through tests, observations, questionnaires and documentation. To ensure the validity of the data used data triangulation technique. The results showed in teaching microeconomics matter of supply and demand are increased activity and students learning outcomes in each cycle using scaffolding approach.